Negotiating Identity and Learning Spaces among Marginalized Urban Youth in Informal Education Settings - Sadat, Fahad Achmad; Aminuddin, Aminuddin; Bakri, Bakri (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study analyzes how marginalized urban adolescents negotiate their identities through participation in informal learning spaces and how social interaction dynamics within these spaces influence learning and self-recognition. Using a qualitative case study approach, the research was conducted in an informal education community in Cirebon City involving 20 informants, including adolescents, community facilitators, and non-formal educators. Data were collected through in-depth interviews, participant observations, and community document analysis, then examined using thematic analysis. The findings reveal that informal learning spaces act as arenas for identity negotiation, enabling adolescents to build self-confidence, expand social networks, and develop life-relevant skills. Moreover, informal education helps reduce social stigma by providing a safe environment for self-expression and active participation. In conclusion, the study offers theoretical insights into the relationship between identity and learning spaces and provides practical implications for designing informal education programs that are inclusive, transformative, and empower marginalized urban youth.